'I cry every day': experiences of patients co‐infected with HIV and multidrug‐resistant tuberculosis. Issue 9 (10th July 2013) - Isaakidis, Petros; Rangan, Sheela; Pradhan, Anagha; Ladomirska, Joanna; Reid, Tony; Kielmann, Karina
Abstract Objectives To understand patients' challenges in adhering to treatment for MDR‐TB/HIV co‐infection within the context of their life circumstances and access to care and support. Methods Qualitative study using in‐depth interviews with 12 HIV/MDR‐TB co‐infected patients followed in a Médecins Sans Frontières (MSF) clinic in Mumbai, India, five lay caregivers and ten health professionals. The data were thematically analysed along three dimensions of patients' experience of being and staying on treatment: physiological, psycho‐social and structural. Results By the time patients and their families initiate treatment for co‐infection, their financial and emotional resources were often depleted. Side effects of the drugs were reported to be severe and debilitating, and patients expressed the burden of care and stigma on the social and financial viability of the household. Family caregivers were crucial to maintaining the mental and physical health of patients, but reported high levels of fatigue and stress. Médecins Sans Frontières providers recognised that the barriers to patient adherence were fundamentally social, rather than medical, yet were limited in their ability to support patients and their families. Conclusions The treatment of MDR‐TB among HIV‐infected patients on antiretroviral therapy is hugely demanding for patients, caregivers and families. Current treatment regimens and case‐holding strategies are resource intensive and require high levels of support from family and lay caregivers to encourage patient adherence and retention in care.